A Post-occupancy Evaluation of Occupant Satisfaction in Green and Conventional Higher Educational Buildings. Issue 1 (1st January 2022) - Zhao, Yuanhong; Yang, Qingping
Abstract: Post-occupancy evaluation (POE) is a method for measuring building performance in terms of meeting design intent, and identifying any gaps between actual and modelled performances in the of aspects indoor environmental quality (IEQ), occupant satisfaction, energy consumption, etc. In this paper, a structured POE assessment was conducted using the Building Use Survey (BUS) methodology in two higher educational buildings in the United Kingdom. This study aims to help close the building performance gap, optimize building operation systems, and improve occupants' satisfaction levels. In this research, the questionnaire survey investigated the influences of environmental factors on user satisfaction from the main aspects of building overall design, thermal comfort, perceived control, indoor environment quality for noise, lighting, ventilation, and other non-environmental factors, such as the background information about age, gender, time in buildings, workgroup size, and so on. The results indicate that the occupant satisfaction with the main aspects of building overall design, indoor environment quality, and thermal comfort in summer and winter in both buildings is lower than the benchmark data. The feedback of this POE assessment has been reported to the building management team to allow managers to develop high-performance building operation guidelines to narrow down the performance gap and improve user satisfaction, comfort, and productivity.